(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
This paper studies the Granada urban choreographies inserted in Guerra de Granada within the framework of the renewal of the genre in the second half of the 16th century. This is an aspect of this historical monograph that until now has gone unnoticed by scholars of the work. The changes in chorographic discourse are a consequence of a new understanding of urban space as an intersection of geographical, political, etymological, historiographical and antiquarian aspects. Textual, methodological and rhetorical issues are addressed, as well as their relationship with other choreographies of the time, especially Las Antigüedades de las ciudades de España by Ambrosio de Morales. Finally, it will be explained how Guerra de Granada largely breaks with the conventions of Renaissance chorographic literature, offering a singular and desolate image of Granada, in contrast to the vision it offers of Seville in a second chorography that is antithetical to the first.